Direct and synergistic hemolytic reactions triggered by indoor airborne mold - Mekaprateep, Malee; Chongkae, Siriporn; Vanittanakom, Nongnuch (Biomedical Sciences and Clinical Medicine, 2018)
Objective Adverse human health effects from indoor fungi probably result from exposure to spores, fungal fragments, and their metabolites. Some fungi take advantage of hemolytic factors production for acquisition of the iron required for growth and survival in the host environment. To examine common types of airborne molds and their hemolytic reactions, air samples were collected from buildings in each of three seasons (hot, cool, and rainy) during the period January 2008 to October 2009. Methods Samples were obtained using a modified air collector and the settle plate method. Isolated molds were tested for their ability to produce hemolytic factors directly on complete solid media supplemented with either human or sheep blood. Along with direct hemolytic activity, Aspergillus or Penicillium isolates were simultaneously tested for their cooperative hemolytic (CAMP-like) reactions with four common bacteria found in the respiratory tract. Results Cladosporium was the predominant mold throughout the year, but it was found at higher concentrations in the cool season. It was followed in abundance by Aspergillus, but was found in higher concentrations in the hot and the rainy seasons. One third of the common mold-tested isolates, including Aspergillus, Cladosporium, Fusarium, Penicillium, and non-sporulating mold, could lyse human blood better than sheep blood at 28ºC and/or 37ºC with the exception that all Cladosporium and some Penicillium tested could not grow at 37ºC. Most of the tested mold isolates had synergistic CAMP-like reactions with Staphylococcus aureus or Streptococcus pneumoniae on sheep blood agar, but reactions with Streptococcus pneumoniae were varied. Conclusions Common indoor airborne mold found throughout the year were Cladosporium, Aspergillus, Penicillium, Fusarium, and non-sporulating mold. One third of the common mold-tested isolates had hemolytic activities on human blood better than sheep blood. Most of the Aspergillus and Penicillium isolates had synergistic hemolytic reactions on sheep blood with Staphylococcus aureus.